(untitled) (Modern education and development, 2025)
This article presents a step-by-step process that emphasizes setting clear objectives, developing balanced study plans, and focusing on the four core language skills: listening, speaking, reading, and writing. It highlights the importance of vocabulary expansion, grammar mastery, and leveraging modern technological tools like language apps and online resources.